LITERATURE REVIEW: THE EFFECT OF ANXIETY ON DIGIT SUCKING HABIT AND DENTAL MALOCCLUSION IN CHILDREN - Icca Octa Mevia; Welly Anggarani; Erna Dwi Agustin (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Digit sucking habit in children arised because of early weaning, feeling of afraid, hunger, sleepy, bored, anxiety and other psychological problems. Digit sucking habit that continued until four years of age or older can lead to malocclusion. Malocclusion is an abnormality in the arrangement of teeth associated with changes in the growth and development of the craniofacial system. However, there has been no literature review that discusses this matter. Method: Literature review by conducting a literature search using several data bases, such as Google Scholar, Science Direct, and NCBI. The literature discusses related to, digit sucking habit in children, anxiety that causes finger sucking habits in children and the incidence of malocclusion in children due to finger sucking habits.Discussion: The results of the literature review that have been carried out show that the anxiety experienced by children can cause finger habits as a form of adaptive response to anxiety. Characteristics of malocclusion due to finger sucking habits that are commonly found in children are usually: AOB, posterior crossbite, and overjet.Conclusion: It is very rare to examine the relationship of anxiety in children to finger habits and activities with malocclusion in children, so further research is needed.